Body conformation and robustness as potential frontiers in pasture-based beef cattle breeding: a narrative review - Zindove, Titus J. (Frontiers in Animal Science, 2026)
As the demand for pasture-finished beef continues to grow, the importance of sustainably producing cattle under pasture-based systems has become increasingly evident. The arid and semi-arid environments are very variable and volatile, making cattle robustness an increasingly valuable attribute. The current trend in genetic selection in pasture-based cattle production systems has focused on adaptation among other traits but ignoring the importance of robustness. Robustness is a difficult phenotype to characterise because it is a complex trait composed of multiple components, including dynamic elements such as the rates of response to, and recovery from, environmental perturbations. Further, measuring robustness’ component traits is time-consuming, expensive, and labour intensive. To implement sound and effective selection procedures for robustness in beef cattle, simplified alternative strategies are a necessity. The use of highly heritable and easy to measure conformation traits is one possible alternative pending ascertainment of the relationship between conformation traits and robustness of beef cattle. Indirect selection for robust beef cattle using conformation traits may help to produce environmentally friendly beef cattle that are resilient and able to cope with environmental variations. This review deciphers robustness and conformation of beef cattle and their potential complementarity in selection for resilience to harsh environmental conditions.